Students’ mathematics and real life contexts in solving algebraic word problems - Baidoo, Joseph; Ali, Clement Ayarebilla (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Background: Algebra involves rules of operations, signs of operations, equations, and algebraic structures. Previous studies have indicated that students often struggle with mathematics in both academic and real-life contexts.Aim: The main objective of this study was to explore how students handle word problems in both mathematics and real-life contexts.Method: The study utilized a cross-sectional design to examine these issues in the developing world, specifically targeting junior high school students in Ghana. A total of 200 students, comprising 91 males and 109 females from various public Junior High Schools, were randomly sampled. The research categorized problems into mathematics context and real-life context, with analysis further divided into 'attempt statuses' (either 'attempted' or 'not attempted') and 'performance statuses' (either 'correct' or 'wrong'). Follow-up interviews, each lasting 15 minutes, were conducted with three groups of both male and female students.Results: The results from the independent samples t-test revealed that the mean score for male students (M =15.37, SD =3.435) was not significantly different from that of female students (M = 15.35, SD = 3.619). It was observed that male students attempted all word problems, while some problems were not attempted by female students.Conclusion: The study concluded that there is no statistically significant difference in the ability of male and female students to solve algebraic word problems. The lack of attempts by female students on some items suggests a potential lack of understanding in context problems. It is recommended that teachers employ multiple representations, technology tools, and metacognitive strategies to help bridge these gaps.